Kepemimpinan Kepala Sekolah Dalam Pemberdayaan Pegawai di SMA Negeri 8 Pekanbaru - Rosmawati, Rosmawati; Umari, Tri (Pelita Bangsa Pelestari Pancasila, 2009)
Succeding of school organization in reaching target determined by leadership of the headmaster on powered potency of school personal. One of them is potency of school officer. This research target to know the headmaster leadership in order to enableness of school officer. And this research used descriptive methode in which explained how headmaster leadership in powered of school officer. Unit analyzes is a headmaster and school officer of SMA Negeri 8 Pekanbaru. Data gathering technique by holding interview with headmaster and school officer. The result of this research indicated that application of empowerment by influencing, moving and motivating. There are many strategies that used by the headmaster in powerment school officer, there are ; entangling the school officer in doing school program, executing supervision, entangling school officer in committee, giving reinforcement, giving opportunity in servicetraining, inculcating togetherness culture, and also create the atmosphere which conducive by equipping facilities create the clean and fresh environment.